2014
DOI: 10.1007/s00429-014-0713-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of chronic stress along the hippocampal dorsal–ventral axis

Abstract: Stress impacts differently in distinct brain regions. However, so far few studies have focused on the differential responses triggered by stressful stimuli on the intrinsic functional heterogeneity of the hippocampal axis. In this study, we assessed the functional and structural alterations caused by exposure to a chronic unpredictable stress (CUS) paradigm on the dorsal-ventral axis of the hippocampus. The morphological analysis demonstrated that CUS had opposite outcomes in the structure of the dorsal (DH) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 41 publications
(64 reference statements)
6
58
0
1
Order By: Relevance
“…As previously described (Bessa et al, 2009a;Pinto et al, 2014), uCMS-exposed animals presented significantly shorter granule neurons in the dDG compared with CT animals (t 8 ¼ 4.560, p ¼ 0.0019, d ¼ 0.7221; Figure 2a). All ADs, excluding agomelatine, reversed this structural change up to the levels of CT (F (4,21) ¼ 5.344, p ¼ 0.0040, Z 2 ¼ 0.5054; Figure 2a).…”
Section: Neuroplastic Changes In the Hippocampal Dgsupporting
confidence: 81%
See 2 more Smart Citations
“…As previously described (Bessa et al, 2009a;Pinto et al, 2014), uCMS-exposed animals presented significantly shorter granule neurons in the dDG compared with CT animals (t 8 ¼ 4.560, p ¼ 0.0019, d ¼ 0.7221; Figure 2a). All ADs, excluding agomelatine, reversed this structural change up to the levels of CT (F (4,21) ¼ 5.344, p ¼ 0.0040, Z 2 ¼ 0.5054; Figure 2a).…”
Section: Neuroplastic Changes In the Hippocampal Dgsupporting
confidence: 81%
“…Given the evidence for a heterogeneous structure and function along the septotemporal axis of the DG (Kheirbek et al, 2013;Tanti and Belzung, 2013), with the dDG contributing mainly to functions related to learning and memory, whereas the vDG is more related to anxiety and emotional regulation (Tanti and Belzung 2013), we would expect also an impact on the vDG. Moreover, while previous reports have shown that the effects of some AD treatments on adult hippocampal neurogenesis are region specific along the septo-temporal axis of the hippocampus, the implication of morphological changes in granule neurons has not been fully elucidated (Felice et al, 2012;O'Leary et al, 2012), even though a contrasting gradient of stress-induced morphological and physiological changes along the septo-temporal axis of the hippocampus has been shown (Pinto et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Three well-characterized behavioral endpoints (cognition, coping styles, and anxiety) that are disrupted by CUS served as the primary assay endpoints; these were complemented with measures of hippocampal structural and functional integrity. The hippocampus is a central component of the neurocircuitries that control these behaviors and displays overt lesions in both stress-and Tau-related pathologies; in the latter, the hippocampus is one of the earliest brain regions to show signs of neurodegeneration (1,4,7,(10)(11)(12)(13)17). …”
mentioning
confidence: 99%
“…Des modifications de l'hippocampe sont également observées lors de stress intenses et prolongés Pinto et al, 2015;Polan & Hoffer, 2008). Au niveau cortical supérieur, soit les régions du cortex frontal, préfrontal et temporal, une activité métabolique limitée ainsi qu'un développement anormal de la substance blanche sont rapportés chez les enfants institutionnalisés ayant vécu de multiples formes de négligence Govindan, Behen, Helder, Makki, & Chugani, 2010).…”
Section: Les Mécanismes Du Stress Et La Réaction Face Aux Situations unclassified